2013
DOI: 10.1159/000351029
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate Pediatric Thyroid Fine Needle Aspirations: A Study of 68 Cases

Abstract: Objective: The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) provides a reporting scheme for thyroid fine needle aspiration (FNA) and includes three indeterminate categories with different management strategies. This study analyzes indeterminate thyroid FNAs in children, and correlates these findings with the histological features. Methods: A total of 179 thyroid FNA specimens were retrieved from children. Cases were categorized by TBSRTC. Only cases diagnosed as atypia (AUS)/follicular lesion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
2
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(108 citation statements)
references
References 22 publications
7
94
2
5
Order By: Relevance
“…In adults, the risk of malignancy in indeterminate nodules ranges from *5% to 15% in the AUS/FLUS category to 15%-30% in the follicular neoplasm or suggestive of neoplasm group (122). The limited data available suggest these indeterminate FNA categories account for *35% of pediatric FNA and that, in children, 28% of AUS/FLUS lesions and 58% of suggestive of follicular or Hürthle cell neoplasm are malignant (26,124). The 2009 adult guidelines suggested that repeat FNA was an option for adults with indeterminate cytopathology.…”
mentioning
confidence: 99%
“…In adults, the risk of malignancy in indeterminate nodules ranges from *5% to 15% in the AUS/FLUS category to 15%-30% in the follicular neoplasm or suggestive of neoplasm group (122). The limited data available suggest these indeterminate FNA categories account for *35% of pediatric FNA and that, in children, 28% of AUS/FLUS lesions and 58% of suggestive of follicular or Hürthle cell neoplasm are malignant (26,124). The 2009 adult guidelines suggested that repeat FNA was an option for adults with indeterminate cytopathology.…”
mentioning
confidence: 99%
“…Whether the analysis concerns a few thousands [15] or one thousand FNAs [19], the results obtained by researchers working in different parts of the world and staining their specimens with different methods, are quite similar (Papanicolaou stain [18,19,22,23,24,25,26,27,28,29], Giemsa and Papanicolaou stain [19,20,30] and Giemsa stain [20,31,32]). …”
Section: Discussionmentioning
confidence: 99%
“…These studies often come from different medical centres, and the stains vary because of the need to collect a sufficiently large cohort. An overwhelming majority of researchers use Papanicolau stain [5,6,10,14,18,[20][21][22][23][24][25][26][27][28].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Our institution is a comprehensive cancer centre and we perform FNA on all nodules, not only the ones with specific size or radiologic features of malignancy [26,27].…”
Section: Prace Oryginalnementioning
confidence: 99%